Nitrous Oxide Emission from Cropland and Adjacent Riparian Buffers in Contrasting Hydrogeomorphic Settings. Issue 1 (1st January 2014) - Fisher, K.; Jacinthe, P. A.; Vidon, P.; Liu, X.; Baker, M. E.
Abstract : Riparian buffers are important nitrate (NO3 − ) sinks in agricultural watersheds, but limited information is available regarding the intensity and control of nitrous oxide (N2 O) emission from these buffers. This study monitored (December 2009–May 2011) N2 O fluxes at two agricultural riparian buffers in the White River watershed in Indiana to assess the impact of land use and hydrogeomorphologic (HGM) attributes on emission. The study sites included a riparian forest in a glacial outwash/alluvium setting (White River [WR]) and a grassed riparian buffer in tile‐drained till plains (Leary Weber Ditch [LWD]). Adjacent corn ( Zea mays L.) fields were monitored for land use assessment. Analysis of variance identified season, land use (riparian buffer vs. crop field), and site geomorphology as major drivers of N2 O fluxes. Strong relationships between N mineralization and N2 O fluxes were found at both sites, but relationships with other nutrient cycling indicators (C/N ratio, dissolved organic C, microbial biomass C) were detected only at LWD. Nitrous oxide emission showed strong seasonal variability; the largest N2 O peaks occurred in late spring/early summer as a result of flooding at the WR riparian buffer (up to 27.8 mg N2 O–N m −2 d −1 ) and N fertilizer application to crop fields. Annual N2 O emission (kg N2 O–N ha −1 ) was higher in the crop fields (WR: 7.82; LWD: 6.37) than in the riparian areas. A significant difference ( P < 0.02) in annual N2 O emission between the riparian buffers was detected (4.32 vs. 1.03 kg N2 O–N ha −1 at WR and LWD, respectively), and this difference was attributed to site geomorphology and flooding (WR is flood prone; no flooding occurred at tile‐drained LWD). The study results demonstrate the significance of landscape geomorphology and land–stream connection (i.e., flood potential) as drivers of N2 O emission in riparian buffers and therefore argue that an HGM‐based approach should be especially suitable for determination of regional N2 O budget in riparian ecosystems.